Analisis Ujaran Kebencian Pada Kolom Komentar Akun Tiktok Maayang.Lucyana - Enjelita Sormin; Rizka Tri Canty; Rizki Dwi Rahmadayani; Tio Novita Lumban Gaol (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Hate speech is no stranger to us. Hate speech has existed in traditional media before the development of technology as it is now. The type of research used is qualitative with a descriptive method which aims to describe the illocutionary speech acts of hate speech in the comments column on Maayang.Lucyana's Tiktok social network. The data in this study are in the form of words and sentences of Indonesian netizens which are hate speech and are thrown against Mayang in the Tiktok comments column. The data source in this study is Tiktok social media which can be accessed by all parties, in the form of text taken through online searches in the Tiktok Maayang.Lucyana comments column. The data collection technique is obtained from the results of observing and analyzing the evidence of language crimes in the form of hate speech on Indonesian netizens in the comments column on Maayang.Lucyana's Tiktok account. The results of the study reveal that there are expressive, directive, and declarative types of illocutionary speech acts.